Risk Protection System In Sharia Banks In Indonesia - Muslina Muslina (STAI Al-Washliyah Banda Aceh, 2020)
Islamic banking is an institution engaged in the financial sector that is based on sharia principles. This institution operates with many systems not just buy and sell, renting, profit sharing, and other services. Consequently, the risks faced are also very diverse, including financing risk, market risk, liquidity risk, operational risk, compliance risk, legal risk, reputation risk, compliance risk, Rate and Return risk, and Equity Investment Risk. The complexity of the risks faced by Islamic banks makes this institution take a very strict policy in protecting its assets. The policy can consist of financing restructuring, dealing directly with the money market sector, conducting simple transactions, improving the quality of human resources and technology, completing written documents both SOP and others. All was done to maximize risk protection so that public confidence in Islamic banks is increasing. This will make Islamic banks more competitive in competing with conventional banks.